Navigating uncertainty and competing objectives: Spring chinook salmon recovery in the upper Willamette river - Claire E. Couch; J. Rose Wallick; James T. Peterson; Bailey A. Morgan; Matthew L. Keefer; Christopher C. Caudill; Kathleen G. O’Malley; Christina A. Murphy; James S. White; Jake R. Kelley; Dalton J. Hance; Gabriel S. Hansen; et al. (Reviews in Fish Biology and Fisheries, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Early loss of astrocyte p38α MAPK reduces hippocampal neuroinflammation, enhances synaptic strength, and increases non-synaptic mitochondrial uncoupling in female mice during non-pathological aging - Caleb S. Bailey; John C. Gant; Hilaree N. Frazier; Josh M. Morganti; Meggie C. Coleman; Verda A. Davis; Hemendra J. Vekaria; Patrick G. Sullivan; Christopher M. Norris; Linda J. Van Eldik; David J. Braun (GeroScience, 2025)
The p38 mitogen-activated protein kinase has a well-characterized role in modulation of inflammatory processes throughout the body. In the central nervous system, p38 is primarily studied within neurons and microglia, most commonly in the context of neurological insult. The present study was designed to determine its function in astrocytes during non-pathological aging. We generated a conditional knockout model in which a tamoxifen-inducible Aldh1l1 promoter drives Cre recombinase expression in mice with exon 1 of the p38α gene flanked by loxP sites. Knockout of astrocyte p38α was achieved via tamoxifen administration in young sexually mature mice at 3–4 months old. Animals were subsequently aged to 21–24 months prior to performing electrophysiological, immunohistochemical, and biochemical analyses. We found that early loss of astrocyte p38α was associated with a reduction in hippocampal neuroinflammation and concomitant enhancement of synaptic strength in aged female mice. In subsequent experiments in younger animals, the knockout reduced peripheral GFAP levels and increased non-synaptic mitochondrial uncoupling. These findings indicate that astrocyte p38α has wide-ranging effects on brain metabolism, inflammation, and synaptic function during the course of normal aging, including release of GFAP from the central nervous system to the periphery. Follow-up studies exploring the role of astrocyte p38α in various age-associated neuropathological contexts are warranted.

Vaccination against Hendra virus of previously unvaccinated mares and their foals demonstrates the effectiveness of the current prime and boost vaccination schedule for foals - Kimberley J. Carey; Ina Smith; Carol A. Hartley; Kirsten E. Bailey; Kath McIntosh; Christopher C. Broder; James R. Gilkerson (Veterinary Microbiology, 2025)

DNA damage response inhibition is an early event in cadmium-induced breast carcinogenesis - Alexandra N. Nail; Ashley V. Chavez; Aliyah N. Bailey; Mayukh Banerjee; Jared L. Scott; Shelia D. Thomas; J. Christopher States (Toxicology and Applied Pharmacology, 2025)

Integration of crop modeling and sensing into molecular breeding for nutritional quality and stress tolerance - Jonathan Berlingeri; Abelina Fuentes; Earl Ranario; Heesup Yun; Ellen Y. Rim; Oscar Garrett; Alexander Howard; Mary-Francis LaPorte; Sassoum Lo; Duke Pauli; Jenna Hershberger; Mason Earles; et al. (Theoretical and Applied Genetics, 2025)
Integrating innovative technologies into plant breeding is critical to bolster food and nutritional security under biotic and abiotic stresses in changing climates. While breeding efforts have focused primarily on yield and stress tolerance, emerging evidence highlights the need to also prioritize nutritional quality. Advanced molecular breeding approaches have enhanced our ability to develop improved crop varieties and could be substantially informed by the routine integration of crop modeling and remote sensing technologies. This review article discusses the potential of combining crop modeling and sensing with molecular breeding to address the dual challenge of nutritional quality and stress tolerance. We provide overviews of stress response strategies, challenges in breeding for quality traits, and the use of environmental data in genomic prediction. We also describe the status of crop modeling and sensing technologies in grain legumes, rice, and leafy greens, alongside the status of -omics tools in these crops and the use of AI with directed evolution to identify novel resistance genes. We describe the pairwise and three-way integration of AI-enabled sensing and biophysically and empirically constrained crop modeling into breeding to enable prediction of phenotypic and breeding values and dissection of genotype-by-environment-by-management interactions with increasing fidelity, efficiency, and temporal/spatial resolution to inform selection decisions. This article highlights current initiatives and future trends that focus on leveraging these advancements to develop more climate-resilient and nutritionally dense crops, ultimately enhancing the effectiveness of molecular breeding.

Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluation of six sugar kelp crosses selected for high yield at three Northeastern US farms - Sara T. Gonzalez; Yaoguang Li; Margaret Aydlett; David Bailey; Hadley Kerr; Michael Doall; Christopher J. Gobler; Michael Chambers; Jean-Luc Jannink; Charles Yarish; Scott Lindell (Aquaculture, 2025)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Foals of mares vaccinated for Hendra virus have a suboptimal response to HeV vaccination - Kimberley J. Carey; Ina Smith; Jennifer Barr; Sarah Caruso; Gough G. Au; Carol A. Hartley; Kirsten E. Bailey; Wendy Perriam; Christopher C. Broder; James R. Gilkerson (Veterinary Microbiology, 2024)

The complex continental margin of NE Oman: Fault-gouge dating of the Wadi Kabir Fault at the northern margin of the Saih Hatat window, Sultanate of Oman, and its wider implications - Uwe Ring; Tonguc Uysal; Reuben J. Hansman; Andreas Scharf; Christopher Bailey; Frank Mattern; Ivan Callegari; Kui Tong; Andrew Todd (Journal of Asian Earth Sciences, 2024)

Comparing inactivation of Escherichia coli O157:H7 on fresh produce using plasma-activated mist - Jinjie He; Sidney Ortiz; Sudipti Attri; Charles Bailey; Alexander Rabinovich; Alexander Fridman; Gregory Fridman; Christopher M. Sales (Innovative Food Science & Emerging Technologies, 2024)

Telomeres and aging: on and off the planet! - Christopher E. Mason; Maria A. Sierra; Henry J. Feng; Susan M. Bailey (Biogerontology, 2024)
Improving human healthspan in our rapidly aging population has never been more imperative. Telomeres, protective “caps” at the ends of linear chromosomes, are essential for maintaining genome stability of eukaryotic genomes. Due to their physical location and the “end-replication problem” first envisioned by Dr. Alexey Olovnikov, telomeres shorten with cell division, the implications of which are remarkably profound. Telomeres are hallmarks and molecular drivers of aging, as well as fundamental integrating components of the cumulative effects of genetic, lifestyle, and environmental factors that erode telomere length over time. Ongoing telomere attrition and the resulting limit to replicative potential imposed by cellular senescence serves a powerful tumor suppressor function, and also underlies aging and a spectrum of age-related degenerative pathologies, including reduced fertility, dementias, cardiovascular disease and cancer. However, very little data exists regarding the extraordinary stressors and exposures associated with long-duration space exploration and eventual habitation of other planets, nor how such missions will influence telomeres, reproduction, health, disease risk, and aging. Here, we briefly review our current understanding, which has advanced significantly in recent years as a result of the NASA Twins Study, the most comprehensive evaluation of human health effects associated with spaceflight ever conducted. Thus, the Twins Study is at the forefront of personalized space medicine approaches for astronauts and sets the stage for subsequent missions. We also extrapolate from current understanding to future missions, highlighting potential biological and biochemical strategies that may enable human survival, and consider the prospect of longevity in the extreme environment of space.

Effects of forest management on private lands in West Virginia on Cerulean Warblers (Setophaga cerulea) and the avian community - Lincoln R. Oliver; Richard S. Bailey; Kyle.R. Aldinger; Petra B. Wood; Christopher M. Lituma (Forest Ecology and Management, 2024)

Smartwatch-Based Prediction of Single-Stride and Stride-to-Stride Gait Outcomes Using Regression-Based Machine Learning - Christopher A. Bailey; Alexandre Mir-Orefice; Thomas K. Uchida; Julie Nantel; Ryan B. Graham (Annals of Biomedical Engineering, 2023)

Concentrations of penicillin and gentamicin following intrauterine administration of two compounded formulations - Theresa M Beachler; Mark G Papich; Larry W Wulf; Debosmita Kundu; Jonathan P Mochel; Katie E Withowski; Christopher S Bailey (Journal of Equine Veterinary Science, 2023)

Beauty in biology: An empirical assessment - Brandon Vaidyanathan; Bailey Haraburda; Christopher Justin Jacobi (Journal of Biosciences, 2023)

The peroxidase response of Alternanthera philoxeroides (Alligator Weed) and Nasturtium officinale (Watercress) to heavy metal exposure - Christopher Beals; Hannah King; Ginger Bailey (Environmental Science and Pollution Research, 2023)

Low diversity and microdiversity of comammox bacteria in wastewater systems suggest specific adaptations within the Ca. Nitrospira nitrosa cluster - Irmarie Cotto; Katherine J. Vilardi; Linxuan Huo; Emily C. Fogarty; Wendell Khunjar; Christopher Wilson; Haydee De Clippeleir; Kevin Gilmore; Erika Bailey; Sebastian Lücker; Ameet J. Pinto (Water Research, 2023)

Cerebrovascular function and its association with systemic artery function and stiffness in older adults with and without mild cognitive impairment - Tom G. Bailey; Timo Klein; Annelise L. Meneses; Kayla B. Stefanidis; Stefanie Ruediger; Daniel J. Green; Tim Stuckenschneider; Stefan Schneider; Christopher D. Askew (European Journal of Applied Physiology, 2022)
Purpose Our aim was to compare cerebrovascular and systemic vascular function between older adults with and without mild cognitive impairment (MCI), and to determine which measures of vascular function best predict the presence of MCI. Methods In 41 adults with MCI and 33 adults without MCI (control) we compared middle cerebral artery velocity (MCAv) and cerebrovascular pulsatility index (PI) at rest, cerebrovascular reactivity to CO 2 , and responsiveness to changes in blood pressure (%∆MCAv/%∆MAP). Systemic vascular function was assessed by flow-mediated dilation (FMD) and stiffness by pulse wave velocity (PWV). Results Cerebrovascular PI was higher in MCI compared with control (mean ± SD: 1.17 ± 0.27 vs. 1.04 ± 0.21), and MCI exhibited a lower %∆MCAv/%∆MAP (1.26 ± 0.44 vs. 1.50 ± 0.55%). Absolute ( p = 0.76) and relative cerebrovascular reactivity to CO 2 ( p = 0.34) was similar between MCI and control. When age was included as a covariate the significant difference in cerebral PI between groups was lost. PWV was higher (13.2 ± 2.2 vs. 11.3 ± 2.5 m s −1 ) and FMD% (4.41 ± 1.70 vs. 5.43 ± 2.15%) was lower in MCI compared with control. FMD% was positively associated with PI across the cohort. Logistic regression analysis indicated that FMD and PWV significantly discriminated between MCI and controls, independent of age, whereas the inclusion of cerebrovascular measures did not improve the predictive accuracy of the model. Conclusion These findings raise the possibility that early changes in systemic vascular stiffness and endothelial function may contribute to altered cerebrovascular haemodynamics and impaired cognitive function, and present potential targets for prevention and treatment strategies in people with MCI.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The impact of the COVID-19 pandemic on a recreational rainbow trout (Oncorhynchus mykiss) fishery - Christopher M. Bunt; Bailey Jacobson (Environmental Biology of Fishes, 2022)

Site fidelity and seasonal habitat preferences of largemouth bass (Micropterus salmoides) in a temperate regulated reservoir - Christopher M. Bunt; Bailey Jacobson; Timothy Fernandes; Luke Ridgway; Bailey McMeans (Hydrobiologia, 2021)

Exposure to a common urban pollutant affects the survival and swimming behaviour of c reek c hub ( Semotilus atromaculatus ) - Christopher M. Bunt; Bailey Jacobson (Journal of Fish Biology, 2021)
Anthropogenic effects on the aquatic environment are ever present and ever increasing and while a plethora of aquatic contaminants are known to affect fishes, one ubiquitous and increasingly prevalent world‐wide urban runoff pollutant is frequently disregarded, and that is pet waste. While dog waste has been identified as a significant factor contributing to bacteria and nutrient loading within receiving waters and the associated water quality changes are known to affect fishes, the impact of uncollected dog faeces on urban fish populations has never been directly investigated. In this study we exposed creek chub ( Semotilus atromaculatus ), a widespread tolerant stream minnow, to various realistic concentrations of dog waste as simulated urban park runoff testing both fresh and dried dog faeces in both stagnant and aerated water for 96 h to investigate the impact on fish survival and behaviour. Creek chub percentage mortality increased significantly relative to controls and across an exposure gradient and was likely caused by anoxic conditions. Survivors were initially smaller while those that died were initially larger and presented with abnormal abdominal subdermal lesions post‐exposure. Additional indicators of physiological stress included significantly increased rates of aquatic surface respiration and changes in flume test derived swimming motivation metrics with increased exposure concentrations. Both mortality and behavioural responses were alleviated by aeration. Furthermore, trials with fresh and dried faeces differed only in time‐to‐death and swimming metrics where results from dried trials were similar to those from aerated experiments. Results demonstrated the impact that the global dog waste management problem can have on aquatic communities with effects on creek chub likely to be more severe for less pollution‐tolerant species and also likely to be exacerbated under future scenarios that consider climate change and increased urbanization.

Early Ecosystem Development Varies With Elevation and Pre-Restoration Land Use/Land Cover in a Pacific Northwest Tidal Wetland Restoration Project - Christopher N. Janousek; Scott J. Bailey; Laura S. Brophy (Estuaries and Coasts, 2021)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Characterization of Concussive Events in Professional American Football Using Videogrammetry - Ann M. Bailey; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Neal Carter; David Hessel; Stephen Beier; William Neale (Annals of Biomedical Engineering, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Vagococcus salmoninarum I—A chronic coldwater streptococcosis in broodstock brook trout ( Salvelinus fontinalis ) in Wisconsin, USA - Isaac Standish; Sara Erickson; Eric Leis; Wes Baumgartner; Thomas Loch; Christopher Knupp; Rebekah McCann; Corey Puzach; Ryan Katona; Ellen Lark; Jennifer Bailey; Jorge Buening; et al. (Journal of Fish Diseases, 2020)
In 2018, Vagococcus salmoninarum was isolated from two lots of broodstock “coaster” brook trout ( Salvelinus fontinalis ) containing ~1,500 fish at the Iron River National Fish Hatchery, at which time it was identified as the causative agent of a chronic coldwater streptococcosis epizootic. Clinical signs included exophthalmia, lethargy, erratic swimming and loss of equilibrium. Female fish experienced disproportionately higher morbidity and mortality than male co‐inhabitants, and routinely retained eggs following spawning. The most consistent gross clinical sign was heart pallor and turbid pericardial effusion. An attempted treatment using florfenicol was ineffective at halting the epizootic, which spanned more than a year and resulted in >50% mortality before remaining fish were culled. As there is no previous documentation of V. salmoninarum at this hatchery or in this species, it is still unclear what circumstances led to this epizootic. The inability to treat this chronic disease led to the loss of valuable broodstock, hampering ongoing fishery conservation efforts in the Great Lakes Basin.

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities - Aloysius T.M. van Helmond; Lars O. Mortensen; Kristian S. Plet‐Hansen; Clara Ulrich; Coby L. Needle; Daniel Oesterwind; Lotte Kindt‐Larsen; Thomas Catchpole; Stephen Mangi; Christopher Zimmermann; Hans Jakob Olesen; Nick Bailey; et al. (Fish and Fisheries, 2020)
Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despite its advantages, and its global use for monitoring, progresses in implementation in some important fishing regions are slow. Within this context, the second objective was to discuss more specifically the European experiences gained through 16 trials. Findings show that the three major benefits of EM were as follows: (a) cost‐efficiency, (b) the potential to provide more representative coverage of the fleet than any observer programme and (c) the enhanced registration of fishing activity and location. Electronic monitoring can incentivize better compliance and discard reduction, but the fishing managers and industry are often reluctant to its uptake. Improved understanding of the fisher's concerns, for example intrusion of privacy, liability and costs, and better exploration of EM benefits, for example increased traceability, sustainability claims and market access, may enhance implementation on a larger scale. In conclusion, EM as a monitoring tool embodies various solid strengths that are not diminished by its weaknesses. Electronic monitoring has the opportunity to be a powerful tool in the future monitoring of fisheries, particularly when integrated within existing monitoring programmes.

Assessing the Effects of Climate Change and Air Pollution on Soil Properties and Plant Diversity in Northeastern U.S. Hardwood Forests: Model Setup and Evaluation - Salim Belyazid; Jennifer Phelan; Bengt Nihlgård; Harald Sverdrup; Charles Driscoll; Ivan Fernandez; Julian Aherne; Leslie M. Teeling-Adams; Scott Bailey; Matt Arsenault; Natalie Cleavitt; Brett Engstrom; et al. (Water, Air, & Soil Pollution, 2019)

Climate‐driven reduction of genetic variation in plant phenology alters soil communities and nutrient pools - Ian M. Ware; Michael E. Van Nuland; Jennifer A. Schweitzer; Zamin Yang; Christopher W. Schadt; Lindsay C. Sidak‐Loftis; Nathan E. Stone; Joseph D. Busch; David M. Wagner; Joseph K. Bailey (Global Change Biology, 2019)
We examined the hypothesis that climate‐driven evolution of plant traits will influence associated soil microbiomes and ecosystem function across the landscape. Using a foundation tree species, Populus angustifolia , observational and common garden approaches, and a base population genetic collection that spans 17 river systems in the western United States, from AZ to MT, we show that (a) as mean annual temperature (MAT) increases, genetic and phenotypic variation for bud break phenology decline; (b) soil microbiomes, soil nitrogen (N), and soil carbon (C) vary in response to MAT and conditioning by trees; and (c) with losses of genetic variation due to warming, population‐level regulation of community and ecosystem functions strengthen. These results demonstrate a relationship between the potential evolutionary response of populations and subsequent shifts in ecosystem function along a large temperature gradient.

Effects of exercise intensity and cardiorespiratory fitness on the acute response of arterial stiffness to exercise in older adults - Maria Perissiou; Tom G. Bailey; Mark Windsor; Michael Chi Yuan Nam; Kim Greaves; Anthony S. Leicht; Jonathan Golledge; Christopher D. Askew (European Journal of Applied Physiology, 2018)

Phylogeny is a powerful tool for predicting plant biomass responses to nitrogen enrichment - Rachel C. Wooliver; Zachary H. Marion; Christopher R. Peterson; Brad M. Potts; John K. Senior; Joseph K. Bailey; Jennifer A. Schweitzer (Ecology, 2017)
Increasing rates of anthropogenic nitrogen (N) enrichment to soils often lead to the dominance of nitrophilic plant species and reduce plant diversity in natural ecosystems. Yet, we lack a framework to predict which species will be winners or losers in soil N enrichment scenarios, a framework that current literature suggests should integrate plant phylogeny, functional tradeoffs, and nutrient co‐limitation. Using a controlled fertilization experiment, we quantified biomass responses to N enrichment for 23 forest tree species within the genus Eucalyptus that are native to Tasmania, Australia. Based on previous work with these species' responses to global change factors and theory on the evolution of plant resource‐use strategies, we hypothesized that (1) growth responses to N enrichment are phylogenetically structured, (2) species with more resource‐acquisitive functional traits have greater growth responses to N enrichment, and (3) phosphorus (P) limits growth responses to N enrichment differentially across species, wherein P enrichment increases growth responses to N enrichment more in some species than others. We built a hierarchical Bayesian model estimating effects of functional traits (specific leaf area, specific stem density, and specific root length) and P fertilization on species' biomass responses to N, which we then compared between lineages to determine whether phylogeny explains variation in responses to N. In concordance with literature on N limitation, a majority of species responded strongly and positively to N enrichment. Mean responses ranged three‐fold, from 6.21 ( E. pulchella ) to 16.87 ( E. delegatensis ) percent increases in biomass per g N·m −2 ·yr −1 added. We identified a strong difference in responses to N between two phylogenetic lineages in the Eucalyptus subgenus Symphyomyrtus , suggesting that shared ancestry explains variation in N limitation. However, our model indicated that after controlling for phylogenetic non‐independence, eucalypt responses to N were not associated with functional traits (although post‐hoc analyses show a phylogenetic pattern in specific root length similar to that of responses to N), nor were responses differentially limited by P. Overall, our model results suggest that phylogeny is a powerful predictor of winners and losers in anthropogenic N enrichment scenarios in Tasmanian eucalypts, which may have implications for other species.

Post Mortem Human Surrogate Injury Response of the Pelvis and Lower Extremities to Simulated Underbody Blast - Ann M. Bailey; John J. Christopher; Frederick Brozoski; Robert S. Salzar (Annals of Biomedical Engineering, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Improved Meta-Analytic Methods Show No Effect of Chromium Supplements on Fasting Glucose - Christopher H. Bailey (Biological Trace Element Research, 2014)

Taxon‐ and vector‐specific variation in species richness and abundance during the transport stage of biological invasions - Elizabeta Briski; Sarah A. Bailey; Oscar Casas-Monroy; Claudio DiBacco; Irena Kaczmarska; Janice E. Lawrence; Jonas Leichsenring; Colin Levings; Michael L. MacGillivary; Christopher W. McKindsey; Leslie E. Nasmith; Marie Parenteau; et al. (Limnology and Oceanography, 2013)
Recent empirical and statistical evidence suggest that propagule pressure (i.e., number of individuals introduced per event, and the number and frequency of events) and colonization pressure (i.e., number of species released per event, and the number and frequency of events) are of vital importance to invasion success. To explore possible changes in propagule and colonization pressure during the transport stage of the invasion process, we examine abundance and species richness of virus‐like particles, bacteria, diatoms, dinoflagellates, and invertebrates transported in commercial ships—a leading vector for global spread of aquatic nonindigenous species. We collected 154 ballast water samples from ships that had performed or were exempt from ballast water exchange (BWE) prior to arrival at Pacific and Atlantic ports in Canada and Laurentian Great Lakes ports. We found that abundance and species richness varied across taxa and regions, with ships arriving to the Atlantic region carrying the highest abundance of taxa. The highest species richness of invertebrates and diatoms was recorded from ships arriving to the Pacific, whereas the richest communities of dinoflagellates occurred in the Atlantic region. We also found that BWE had no effect on abundance or species richness of most taxa (dinoflagellates, diatoms, bacteria, and virus‐like particles), whereas the effect on abundance of invertebrates was not clear. Finally, longer voyages resulted in lower abundance of all taxa except dinoflagellates, and lower species richness of diatoms. Paradoxically, the elevated abundance and species richness of dinoflagellates following BWE suggest that this group could have enhanced invasion potential when ships manage ballast water by exchange.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Mechanisms and performance measures in mastery-based incremental repeated acquisition: behavioral and pharmacological analyses - Jordan M. Bailey; Joshua E. Johnson; M. Christopher Newland (Psychopharmacology, 2010)

Mortality Gradients within and among Dominant Plant Populations as Barometers of Ecosystem Change During Extreme Drought - ALICYN R. GITLIN; CHRISTOPHER M. STHULTZ; MATTHEW A. BOWKER; STACY STUMPF; KRISTINA L. PAXTON; KARLA KENNEDY; AXHEL MUÑOZ; JOSEPH K. BAILEY; THOMAS G. WHITHAM (Conservation Biology, 2006)
Understanding patterns of plant population mortality during extreme weather events is important to conservation planners because the frequency of such events is expected to increase, creating the need to integrate climatic uncertainty into management. Dominant plants provide habitat and ecosystem structure, so changes in their distribution can be expected to have cascading effects on entire communities. Observing areas that respond quickly to climate fluctuations provides foresight into future ecological changes and will help prioritize conservation efforts. We investigated patterns of mortality in six dominant plant species during a drought in the southwestern United States. We quantified population mortality for each species across its regional distribution and tested hypotheses to identify ecological stress gradients for each species. Our results revealed three major patterns: (1) dominant species from diverse habitat types (i.e., riparian, chaparral, and low‐ to high‐elevation forests) exhibited significant mortality, indicating that the effects of drought were widespread; (2) average mortality differed among dominant species (one‐seed juniper [Juniperus monosperma (Engelm.) Sarg.] 3.3%; manzanita [Arctostaphylos pungens Kunth], 14.6%; quaking aspen [Populus tremuloides Michx.], 15.4%; ponderosa pine [Pinus ponderosa P. & C. Lawson], 15.9%; Fremont cottonwood [Populus fremontii S. Wats.], 20.7%; and pinyon pine [Pinus edulis Engelm.], 41.4%); (3) all dominant species showed localized patterns of very high mortality (24–100%) consistent with water stress gradients. Land managers should plan for climatic uncertainty by promoting tree recruitment in rare habitat types, alleviating unnatural levels of competition on dominant plants, and conserving sites across water stress gradients. High‐stress sites, such as those we examined, have conservation value as barometers of change and because they may harbor genotypes that are adapted to climatic extremes.

Bacterial diversity is determined by volume in membrane bioreactors - Christopher J. Van Der Gast; Bruce Jefferson; Elizabeth Reid; Tim Robinson; Mark J. Bailey; Simon J. Judd; Ian P. Thompson (Environmental Microbiology, 2006)
Summary It has been proposed that established models and theories developed in classical ecology could be employed to greatly improve the optimization of wastewater treatment plants (WWTP) by placing the microbiological component onto a model‐predictive basis. In particular, this could be achieved by better understanding bacterial community assembly and development. The species–area relationship is one of the oldest biological laws and has been used to describe spatial diversity patterns in contiguous habitats and on islands. In the current study, bacterial communities in seven membrane bioreactors (MBR), of increasing size, located across the UK were sampled. A significant linear relationship between bacterial taxa richness and reactor size was observed and was similar to classical species–area relationships of larger organisms colonizing oceanic islands. Rank‐abundance plots revealed a gradient of greater evenness in community structure as MBR volume increased. Application of the Raup and Crick probability‐based similarity index indicated a strong role for dispersal in MBR colonization and community structure. Our findings demonstrate that the MBR sampled behaved like islands with respect to bacterial colonization in accordance with the theory of island biogeography. In addition this study provides further evidence that biodiversity at the bacterial level is more similar to that of animals and plants than previously postulated.

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

The natriuretic effect of glibenclamide: evidence for a non-luminal site of action - Matthew Bailey; David Shirley; Christopher Stocking; Jonathan Slater; Stephen Walter (Pflügers Archiv - European Journal of Physiology, 2002)

Transport properties of N-acyl derivatives of the coprogen and ferrichrysin classes of siderophores inNeurospora crassa - Carl J. Carrano; Christopher T. Bailey; Joseph A. Bonadies (Archives of Microbiology, 1986)

A possible rôle for acid phosphatase in γ-amino-n-butyrate uptake in Aspergillus nidulans - Herbert N. Arst; Christopher R. Bailey; Hugh A. Penfold (Archives of Microbiology, 1980)